Characterization of a Murine Anti-laminin-1 Monoclonal Antibody (AK8) Produced by Immunization with Mouse-derived Laminin-1 - Akane Kondo; Junko Inagaki; Kazuko Kobayashi; Hideo Tsukamoto; Daisuke Yamamoto; Mikiya Nakatsuka; Nobuharu Suzuki; Motoyoshi Nomizu; Satoshi Amano; Hidehiko Matsubayashi; Tatsuji Yasuda; Luis R. Lopez; et al. (Clinical and Developmental Immunology)
Laminin-1 is a structural glycoprotein that forms an integral part of the scaffolding of basement membranes, and plays an important role during embryonic development. We have recently demonstrated a significant association between anti-laminin-1 antibodies (Abs) and reproductive failure, such as recurrent spontaneous abortions and infertility-associated endometriosis in both human and mouse studies. In the present study, we established an IgM (μ,κ) monoclonal anti-laminin-1 Ab (AK8) by immunizing mice with mouse Engelbreth-Holm-Swarm sarcoma (EHS)-derived laminin-α1. The AK8 monoclonal antibody (mAb) reacted with particular peptide sequences from the globular G domain of mouse laminin-α1 chain of using ELISA and Western blot techniques. The peptide tertiary structure of the epitope recognized by AK8 mAb was predicted using eight synthesized domain peptide sequences and three consensus sequences obtained by phage displayed random peptide library. Basement membranes of endometrium of pregnant mice and humans were immunostained with AK8 mAb. Thus, AK8 mAb recognized a common structure present in the G domain of the laminin-1 chain in both mice and humans. The passive immunization of mice with AK8 mAb may represent a suitable animal model for anti-laminin-1 Ab-mediated reproductive failure.